Pengaruh Implementasi Green Supply Chain Management terhadap Kinerja Bisnis dalam Perspektif Inbound - Bagus Hari Nugroho; Nufa Visca Amaratya (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to examine the effect of Green Supply Chain Management (GSCM) implementation on business performance with a focus on the inbound perspective. GSCM refers to the application of sustainability principles in supply chain management, including environmentally friendly resource management and energy efficiency. This study was conducted using a quantitative approach through a survey of 120 companies implementing GSCM in the manufacturing sector. Data were collected through a questionnaire measuring aspects of GSCM implementation and business performance related to inbound logistics. Multiple linear regression analysis shows that GSCM implementation significantly affects business performance, particularly in terms of cost reduction, improved operational efficiency, and enhanced corporate reputation. The findings emphasize the importance of GSCM strategies in improving business performance through more effective inbound management. This research provides recommendations for companies to further integrate green principles in their supply chain strategies to achieve better performance benefits.